2015
DOI: 10.1111/joca.12068
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of Financial Well‐Being: Insights into the Role of Executive Function, Financial Socialization, and Experience‐Based Learning in Childhood and Youth

Abstract: During childhood and youth we build the foundations for financial well‐being later in life, acquiring the knowledge, skills, attitudes, and personality traits that enable us to manage our finances as adults. This article reviews literature from consumer science, developmental psychology, and allied fields to gain insight into moments during youthful development when interventions are likely to have greatest impact. We find promising avenues for influence during each developmental life stage. Many present truly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(213 citation statements)
references
References 77 publications
10
171
1
5
Order By: Relevance
“…However, our results should not be taken to mean that parental influence only takes during adolescence. In fact, children could start to develop general skills at a very young age (Drever et al ; Whitebread and Bingham ) and parental financial socialization could also begin as early as before children start school (Drever et al ; McNeal and Yeh ). It is possible that the parental influence observed in our sample is the result of parental financial socialization at earlier stage if parents' financial behavior and children's self‐control skill are stable through time.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results should not be taken to mean that parental influence only takes during adolescence. In fact, children could start to develop general skills at a very young age (Drever et al ; Whitebread and Bingham ) and parental financial socialization could also begin as early as before children start school (Drever et al ; McNeal and Yeh ). It is possible that the parental influence observed in our sample is the result of parental financial socialization at earlier stage if parents' financial behavior and children's self‐control skill are stable through time.…”
Section: Discussionmentioning
confidence: 99%
“…The way that family members communicate about financial matters, for example, will be relevant (see, e.g., Koerner and Fitzpatrick for a review on consumer family communication patterns). In addition, the quality of interpersonal family relationships will be important in order for a successful financial socialization process to develop in a family context (Drever et al ; Gudmunson and Danes ; Kuczynski and Parkin ). Edwards, Allen, and Hayhoe () have demonstrated that parents' financial attitudes and conduct influence the extent to which children are willing to discuss personal finance matters with them.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…Another way to build financial capability is through sound financial advice and guidance, which begin with parents and caregivers. In addition to Drever et al (), who underscore the important role of parents in preparing children for financial functioning, another contribution in the special issue discusses parental influence. Van Campenhout (), in “Revaluing the Role of Parents as Financial Socialization Agents in Youth Financial Literacy Programs,” examines the parental role in helping youth develop financial capability.…”
Section: Action For Financial Capabilitymentioning
confidence: 99%